Microcirculatory Response to Blood vs. Crystalloid Cardioplegia During Coronary Artery BypassGrafting With Cardiopulmonary Bypass - Aykut, Gueclue; Ulugoel, Halim; Aksu, Ugur; Akin, Sakir; Karabulut, Hasan; Alhan, Cem; Toraman, Fevzi; Ince, Can (FRONTIERS MEDIA SA, 2022)
Background: Blood cardioplegia attenuates cardiopulmonary bypass (CPB)-induced systemic inflammatory response in patients undergoing cardiac surgery, which may favorably influence the microvascular system in this cohort. The aim of this study was to investigate whether blood cardioplegia would offer advantages over crystalloid cardioplegia in the preservation of microcirculation in patients undergoing coronary artery bypass grafting (CABG) with CPB.Methods: In this prospective observational cohort study, 20 patients who received crystalloid (n = 10) or blood cardioplegia (n = 10) were analyzed. The microcirculatory measurements were obtained sublingually using incident dark-field imaging at five time points ranging from the induction of anesthesia (T-0) to discontinuation of CPB (T-5).Results: In the both crystalloid {[}crystalloid cardioplegia group (CCG)] and blood cardioplegia {[}blood cardioplegia group (BCG)] groups, perfused vessel density (PVD), total vessel density (TVD), and proportion of perfused vessels (PPV) were reduced after the beginning of CPB. The observed reduction in microcirculatory parameters during CPB was only restored in patients who received blood cardioplegia and increased to baseline levels as demonstrated by the percentage changes from T-0 to T-5 (\%Delta)(T0-T5) in all the functional microcirculatory parameters {[}\%Delta TVDT0-T5(CCG): -10.86 +/- 2.323 vs. \%Delta TVDT0-T5(BCG): 0.0804 +/- 1.107, p < 0.001

\%Delta PVDT0-T5(CCG): -12.91 +/- 2.884 vs. \%Delta PVDT0-T5(BCG): 1.528 +/- 1.144, p < 0.001

\%Delta PPVT0-T5(CCG): -2.345 +/- 1.049 vs. \%Delta PPVT0-T5(BCG): 1.482 +/- 0.576, p < 0.01].Conclusion: Blood cardioplegia ameliorates CPB-induced microcirculatory alterations better than crystalloid cardioplegia in patients undergoing CABG, which may reflect attenuation of the systemic inflammatory response. Future investigations are needed to identify the underlying mechanisms of the beneficial effects of blood cardioplegia on microcirculation.
Keywords: microcirculation; cardiopulmonary bypass; systemic inflammatory response; blood cardioplegia; crystalloid cardioplegia; incident dark-field imaging